2015
DOI: 10.1186/s12348-015-0050-3
|View full text |Cite
|
Sign up to set email alerts
|

Early resolution of subretinal fluid without high-dose corticosteroids in a pregnant patient with Vogt-Koyanagi-Harada disease: a case report

Abstract: BackgroundAt present, there is no standard of treatment using systemic high-dose corticosteroids in cases of pregnant women with Vogt-Koyanagi-Harada (VKH) disease. Although high-dose systemic corticosteroid treatment is often used for VKH disease during pregnancy, it also poses a risk to the fetus.FindingsA 29-year-old woman in the 34th week of pregnancy experienced bilateral metamorphopsia. She had been receiving 5 mg of prednisolone daily for the past 8 years as treatment for rheumatoid arthritis. In order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…What is interesting is the occurrence of inflammation in the second trimester of pregnancy and the rapid resolution of fluid within 2 weeks without treatment, in a patient without a prior history of VKH. However, unlike the case by Sugita et al [ 1 ], our patient did not have any systemic disease and did not receive any corticosteroids in the past. Though it is difficult to explain the observation seen, this case in addition to the case reported by Sugita et al [ 1 ] has shown early resolution of subretinal fluid without treatment in VKH leading us to revisit the role of pregnancy in VKH.…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…What is interesting is the occurrence of inflammation in the second trimester of pregnancy and the rapid resolution of fluid within 2 weeks without treatment, in a patient without a prior history of VKH. However, unlike the case by Sugita et al [ 1 ], our patient did not have any systemic disease and did not receive any corticosteroids in the past. Though it is difficult to explain the observation seen, this case in addition to the case reported by Sugita et al [ 1 ] has shown early resolution of subretinal fluid without treatment in VKH leading us to revisit the role of pregnancy in VKH.…”
mentioning
confidence: 62%
“…However, unlike the case by Sugita et al [ 1 ], our patient did not have any systemic disease and did not receive any corticosteroids in the past. Though it is difficult to explain the observation seen, this case in addition to the case reported by Sugita et al [ 1 ] has shown early resolution of subretinal fluid without treatment in VKH leading us to revisit the role of pregnancy in VKH.
Fig.
…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Studies using Swept Source Optical Coherence Tomography have demonstrated anatomical choroidal remodeling and consistent retinal changes after the use of systemic corticosteroid therapy [ 7 ]. In some cases, observation is the preferred option due to the mothers’ refusal of treatment [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vogt‐Koyanagi‐Harada disease may occur in pregnancy and pose a problem how to apply the standard of care in a pregnant woman 12–14 . In this report, we described a patient who developed Vogt‐Koyanagi‐Harada disease in pregnancy and also summarized 32 patients with the disease in pregnancy in the literature to elucidate the outcome of treatment 15–44 …”
Section: Introductionmentioning
confidence: 99%